Comunidade de prática : narrativas sobre o desenvolvimento profissional do professor iniciante dos anos iniciais na área de Matemática - Carvalho, Andréia Cristina Santiago (2020)
This research is linked to the Postgraduate Program in Education (PPGEdu), in the research line entitled Teacher Education and Education Public Policies of the Federal University of Mato Grosso, Rondonópolis campus. The general objective of this study consists in comprehending the professional development of the beginner teacher of the initial years majored in Full Licentiate in Pedagogy and who participated in the teacher education course about the teaching of mathematics offered by the City Secretary of Education (SEMED), through the Department of Professional Education. This education course was thought in a form of Community of Practice (FIORENTINI, 2013), in which the participants assumed collaborative attitudes with the intention of studying and systematizing paths of teaching and learning mathematics. Therefore, the educational environments are constituted by knowledge interchanges, in an educational movement in which the voices of the teachers are present in the dialogue and in the exchange among peers, in such a way as to deepen the relation and broaden the possibilities of the pedagogical practices. In this perspective, the research is guided by the qualitative approach, having as focus the initial process of the professional development of the beginner teachers who participated in the education course offered by SEMED, in the period of May through June of 2019. In the first semester of 2019, the researcher, who is part of the educational staff of the Department of Professional Education, offered an education course with beginner teachers of the initial years, 1st grade through 3rd of elementary school (with at least 5 years of teaching). It had a total of 30 vacancies, weekly meetings and a workload of 50 hours, in order to develop a Community of Practice, mobilizing studies and constituting systematizations about the ways of teaching and learning mathematics. Thus, the data was gathered in the moments lived in the educational meetings and in the outcome of them in the school environment. Through autobiographic narratives and, every time it was possible and necessary, it were conducted interviews for the complementation and the comprehension of the questions which were left unanswered, the ones that were collected from the participants from this educational process. The data analysis sought to identity and expose, based on the lived experiences in the school environment, as well as in the educational, how the beginner teacher is constituted teacher in the teaching of Mathematics. In addition, it attempted to verify, based on the different narratives, how the participation in the education course offered by SEMED to the beginner teachers who teach Mathematics contribute/contributed to their professional development. It is understood that the education environments propitiated the teachers their participation, reflection and construction of knowledge through the practice of research, understanding that teaching and learning are processes that occur significantly when derive from an investigative attitude of the work conducted in the classroom, involving a continuous process of problematization and deliberation in the school routine. The data point out that the beginner teachers, by participating in the Education Course Community of Practice, showed having understood the necessity of a teaching attitude more active of accountability for their education by enabling that they share experiences, repertoire and knowledge. In a way, it is observed that the subject is constituted teacher in the day by day of the classroom, with the expectations and surprises which they are presented with in the course of their work with the students.